The efficacy of self-exercise in a patient with cervicogenic dizziness: A randomized controlled trial - Piromchai, Patorn; Toumjaidee, Nattaporn; Srirompotong, Somchai; Yimtae, Kwanchanok (Frontiers in Neurology, 2023)
BACKGROUND: Cervicogenic dizziness is a clinical syndrome characterized by neck pain and dizziness. Recent evidence suggested that self-exercise may improve a patient’s symptoms. The objective of this study was to evaluate the efficacy of self-exercise as an add-on therapy in patients with non-traumatic cervicogenic dizziness. METHODS: Patients with non-traumatic cervicogenic dizziness were randomly assigned to the self-exercise and control groups. The self-exercise group was instructed to perform muscle, mobilization, and oculomotor training at home while there was no specific training given to the control group. The neck pain, dizziness symptoms, and their impact on daily life were evaluated by the Dizziness Handicap Inventory (DHI) scale, Neck Disability Index (NDI) scale, and visual analog scale (VAS). The objective outcomes included the range of motion test of the neck and the posturography test. All outcomes were evaluated at 2 weeks after the initial treatment. RESULTS: Thirty-two patients participated in this study. The average age of the participants was 48 years. The DHI score after treatment in the self-exercise group was significantly lower when compared to the control group (mean difference [MD] 25.92 points, 95% CI 4.21 to 47.63, p = 0.021). The NDI score after treatment was also significantly lower in the self-exercise group (MD 6.16 points, 95% CI 0.42 to 11.88, p = 0.036). However, there was no statistical difference in VAS score, range of motion test, and posturography test between the two groups (p > 0.05). No significant side effects were noted in either of the groups. CONCLUSIONS: The self-exercise in non-traumatic cervicogenic dizziness is effective in reducing the dizziness symptoms and its impact on daily life.